Ethylene-allyltrimethylsilane copolymer and preparation method thereof

By using the tetravalent transition metal compound and cocatalyst components in the catalyst composition, the catalytic activity and copolymerization of the ethylene-allyl trimethylsilane copolymer are improved, and the problem of insufficient activity of the existing catalyst is solved, and the problem of achieving the More efficient polymerization.

CN119143910APending Publication Date: 2024-12-17CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310714339.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-15
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing catalysts have insufficient catalytic activity when preparing silicon-containing polymers, making it difficult to meet the needs of efficient copolymerization reactions.

Method used

The catalytic activity and copolymerization are enhanced by copolymerization reaction using a catalyst composition, including a combination of tetravalent transition metal compound and cocatalyst components such as alkyl aluminoxane, organoboron compound and organoaluminum compound.

Benefits of technology

The catalytic activity and copolymerization of ethylene-allyl trimethylsilane copolymer are significantly improved, and the performance of the polymer is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004298577290000021
    Figure BDA0004298577290000021
  • Figure BDA0004298577290000031
    Figure BDA0004298577290000031
  • Figure BDA0004298577290000051
    Figure BDA0004298577290000051
Patent Text Reader

Abstract

The invention relates to the field of olefin polymerization, and discloses an ethylene-allyltrimethylsilane copolymer and a preparation method thereof. In order to achieve the purpose, the preparation method of the ethylene-allyltrimethylsilane copolymer provided by the invention comprises the following steps: ethylene and allyltrimethylsilane are subjected to a copolymerization reaction by using a catalyst composition, and the catalyst composition comprises the following components: a) a transition metal compound; and b) a co-catalyst component. The preparation method of the ethylene-allyltrimethylsilane copolymer disclosed by the invention has the advantage of improving the catalytic activity and the copolymerization property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of olefin polymerization, and in particular to an ethylene-allyltrimethylsilane copolymer and a preparation method thereof. Background Art

[0002] Single-site catalysts for olefin polymerization have been a research hotspot in organometallic chemistry, catalysis, polymer chemistry, and materials science in recent decades. Using this type of catalyst, olefin polymers with uniform molecular weight distribution and chemical composition distribution can be obtained, and the molecular structure and molecular weight of the polymer can be highly controllable by adjusting the catalyst structure. Since this type of catalyst is highly efficient and broad-spectrum when applied to olefin copolymerization (ChemistrySelect 2020, 5, 7581-7585), olefin polymers that cannot be obtained with traditional Ziegler-Natta catalysts can be obtained by using this type of catalyst.

[0003] Non-metallocene transition metal catalysts are important components of single-site catalysts. They have rich ligand structures and simple synthesis processes. Their catalytic performance can be easily adjusted by adjusting the ligand structure (Chemical Reviews, 2003, 103, 283-315).

[0004] Silicon-containing polymers contain silicon elements, so they exhibit good lubricity, adhesion and other surface properties, and are a high-performance polyolefin material.

[0005] At present, the catalytic activity of the catalysts used to prepare silicon-containing polymers is not high enough, and there is still room for further improvement. Summary of the invention

[0006] The object of the present invention is to provide a novel preparation method of ethylene-allyltrimethylsilane copolymer and the prepared ethylene-allyltrimethylsilane copolymer. The preparation method of the ethylene-allyltrimethylsilane copolymer of the present invention has the advantages of improved catalytic activity and copolymerizability.

[0007] In order to achieve the above object, the present invention provides a method for preparing an ethylene-allyltrimethylsilane copolymer, wherein the method comprises: using a catalyst composition to copolymerize ethylene and allyltrimethylsilane,

[0008] Wherein, the catalyst composition comprises the following components:

[0009] a) a transition metal compound having a structure represented by formula (1);

[0010] b) a co-catalyst component,

[0011]

[0012] In formula (1), M is a tetravalent transition metal atom; X and Y are each independently a hydrocarbonoxy group having 1 to 10 carbon atoms or a halogen.

[0013] Preferably, M is a titanium atom, a zirconium atom or a hafnium atom, more preferably a titanium atom or a zirconium atom.

[0014] Preferably, X and Y are each independently a hydrocarbonoxy group having 1 to 6 carbon atoms, a fluorine atom, a chlorine atom, a bromine atom or an iodine atom.

[0015] Preferably, X and Y are each independently a hydrocarbonoxy group having 1 to 3 carbon atoms or a chlorine atom.

[0016] Preferably, the alkoxy group having 1 to 10 carbon atoms is methoxy, ethoxy, propoxy or isopropoxy.

[0017] Preferably, X and Y are both isopropoxy or ethoxy; or, X and Y are both chlorine atoms.

[0018] Preferably, the co-catalyst component comprises an alkylaluminoxane, a combination of an organoboron compound and an organoaluminum compound, or a combination of an organoaluminum compound and an organomagnesium compound.

[0019] Preferably, the co-catalyst component is an alkylaluminoxane, a combination of an organic boron compound and an organic aluminum compound, or a combination of an organic aluminum compound and an organic magnesium compound.

[0020] Preferably, the alkylaluminoxane is a compound selected from the structure represented by formula (2) and / or formula (3),

[0021]

[0022] In formula (2) and formula (3), R is selected from an alkyl group having 1 to 15 carbon atoms, and n represents an integer of 4 to 30.

[0023] Preferably, R is selected from an alkyl group having 1 to 5 carbon atoms, and n represents an integer of 10-30.

[0024] Preferably, the alkylaluminoxane is methylaluminoxane.

[0025] Preferably, the organic boron compound is one or more of triphenylmethyl tetrakis(pentafluorophenyl)borate, N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate and tris(pentafluorophenyl)boron.

[0026] Preferably, the organoaluminum compound is a compound having a structure represented by the general formula AlX1X2X3, wherein X1, X2 and X3 are respectively a halogen atom, an alkyl group having 1-8 carbon atoms, an alkoxy group having 1-8 carbon atoms, and an aryloxy group having 6-12 carbon atoms, and X1, X2 and X3 may be the same or different, and at least one is an alkyl group having 1-8 carbon atoms.

[0027] Preferably, the organoaluminum compound is triisobutylaluminum.

[0028] Preferably, the organic magnesium compound is an organic magnesium compound containing two alkyl groups with carbon atoms of 1-10, preferably an organic magnesium compound containing two alkyl groups with carbon atoms of 1-6, and more preferably di-n-butyl magnesium.

[0029] Preferably, the co-catalyst component is alkylaluminoxane, and the molar ratio of the transition metal compound to the alkylaluminoxane calculated as aluminum is 1:(100-20000), preferably 1:(200-10000), and more preferably 1:(500-5000).

[0030] Preferably, the co-catalyst component is a combination of an organic boron compound and an organic aluminum compound, the molar ratio of the transition metal compound to the organic boron compound is 1:(1-5), preferably 1:(1-2), and the molar ratio of the transition metal compound to the organic aluminum compound is 1:(10-5000), preferably 1:(50-1000), and more preferably 1:(100-500).

[0031] Preferably, the co-catalyst component is a combination of an organic aluminum compound and an organic magnesium compound, the molar ratio of the transition metal compound to the organic aluminum compound is 1:(30-5000), preferably 1:(100-1000), more preferably 1:(100-500), and the molar ratio of the transition metal compound to the organic magnesium compound is 1:(10-2000), preferably 1:(100-1000).

[0032] Preferably, the molar ratio of the organoaluminum compound to the organomagnesium compound is greater than 2.5:1.

[0033] Preferably, the copolymerization temperature is -50 to 200° C., and the copolymerization time is 1 to 300 minutes.

[0034] Preferably, the copolymerization reaction temperature is -20 to 150° C., and the copolymerization reaction time is 5 to 60 minutes.

[0035] Preferably, the concentration of the transition metal compound in the copolymerization reaction system is 1×10 -10 mol / L~1×10 -3 mol / L, preferably 1×10-8 mol / L~1×10 -5 mol / L.

[0036] According to a second aspect of the present invention, there is provided an ethylene-allyltrimethylsilane copolymer prepared by the method for preparing the ethylene-allyltrimethylsilane copolymer according to the first aspect of the present invention.

[0037] Through the above technical scheme, the present invention can provide a new method for preparing ethylene-allyltrimethylsilane copolymer and the prepared ethylene-allyltrimethylsilane copolymer, and the method of the present invention can further improve the catalytic activity and copolymerizability. DETAILED DESCRIPTION

[0038] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0039] The first aspect of the present invention provides a method for preparing an ethylene-allyltrimethylsilane copolymer, wherein the method comprises: using a catalyst composition to copolymerize ethylene and allyltrimethylsilane,

[0040] Wherein, the catalyst composition comprises the following components:

[0041] a) a transition metal compound having a structure represented by formula (1);

[0042] b) a co-catalyst component,

[0043]

[0044] In formula (1), M is a tetravalent transition metal atom; X and Y are each independently a hydrocarbonoxy group having 1 to 10 carbon atoms or a halogen.

[0045] According to the present invention, in formula (1), M is a tetravalent transition metal atom, preferably, M is a titanium atom, a zirconium atom or a hafnium atom; more preferably, M is a titanium atom or a zirconium atom.

[0046] According to the present invention, in formula (1), X and Y are each independently a hydrocarbyloxy group having 1 to 10 carbon atoms or a halogen; preferably, X and Y are each independently a hydrocarbyloxy group having 1 to 6 carbon atoms, a fluorine atom, a chlorine atom, a bromine atom or an iodine atom; more preferably, X and Y are each independently a hydrocarbyloxy group having 1 to 3 carbon atoms or a chlorine atom.

[0047] Examples of the hydrocarbonoxy group having 1 to 10 carbon atoms include methoxy, ethoxy, propoxy, isopropoxy, butoxy, tert-butoxy, sec-butoxy, isobutoxy, pentyloxy, and hexyloxy. Among them, methoxy, ethoxy, propoxy, and isopropoxy are preferred, ethoxy, propoxy, and isopropoxy are more preferred, and ethoxy and isopropoxy are still more preferred.

[0048] Examples of the halogen atom include fluorine, chlorine, bromine and iodine, preferably fluorine, chlorine or bromine, more preferably chlorine or bromine, and particularly preferably chlorine.

[0049] In a particularly preferred embodiment of the present invention, X and Y are both isopropoxy or ethoxy.

[0050] In another particularly preferred embodiment of the present invention, X and Y are both chlorine atoms.

[0051] As specific transition metal compounds, preferably the following compounds can be mentioned:

[0052] In formula (1), M is a titanium atom, and X and Y are both isopropoxy groups;

[0053] In formula (1), M is a titanium atom, and X and Y are both ethoxy groups;

[0054] In formula (1), M is a titanium atom, and X and Y are both chlorine atoms;

[0055] In formula (1), M is a zirconium atom, and X and Y are both isopropoxy groups;

[0056] In formula (1), M is a zirconium atom, and X and Y are both ethoxy groups;

[0057] In formula (1), M is a zirconium atom, and X and Y are both chlorine atoms;

[0058] In formula (1), M is a hafnium atom, and X and Y are both isopropoxy groups;

[0059] In formula (1), M is a hafnium atom, and X and Y are both ethoxy groups;

[0060] In formula (1), M is a hafnium atom, and X and Y are both chlorine atoms.

[0061] According to the present invention, the co-catalyst component can be various co-catalyst components commonly used in the art. Preferably, the co-catalyst component includes a combination of alkylaluminoxane, an organoboron compound and an organoaluminum compound, or a combination of an organoaluminum compound and an organomagnesium compound; more preferably, the co-catalyst component is a combination of alkylaluminoxane, an organoboron compound and an organoaluminum compound, or a combination of an organoaluminum compound and an organomagnesium compound.

[0062] In a particularly preferred embodiment of the present invention, the co-catalyst component is a combination of an organoaluminum compound and an organomagnesium compound, thereby being able to significantly improve the catalytic activity.

[0063] The alkylaluminoxane is preferably a compound selected from the group consisting of compounds represented by formula (2) and / or formula (3).

[0064]

[0065] In formula (2) and formula (3), R is selected from an alkyl group having 1 to 15 carbon atoms, and n is an integer of 4 to 30; more preferably, R is selected from an alkyl group having 1 to 5 carbon atoms, and n is an integer of 10 to 30.

[0066] Specific examples of the above-mentioned alkyl group include methyl, ethyl, propyl, isopropyl, butyl, tert-butyl, sec-butyl, isobutyl, pentyl, 1,1-dimethylpropyl, 1,2-dimethylpropyl, neopentyl, 1-methylbutyl, 2-methylbutyl, isopentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, dodecyl, tridecyl, tetradecyl and pentadecyl.

[0067] Examples of n include 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, and 30.

[0068] Specific examples of the alkylaluminoxane include methylaluminoxane, ethylaluminoxane, propylaluminoxane, and the like. Among them, methylaluminoxane is preferred.

[0069] According to the present invention, the organic boron compound can be various organic boron compounds used as co-catalysts in the art, for example, one or more of triphenylmethyl tetrakis(pentafluorophenyl)borate, N,N-dimethylaniline tetrakis(pentafluorophenyl)borate and tris(pentafluorophenyl)boron.

[0070] According to the present invention, the organoaluminum compound can be various organoaluminum compounds used as co-catalysts in the art. Preferably, the organoaluminum compound is a compound having a structure shown in the general formula AlX1X2X3, wherein X1, X2 and X3 are respectively a halogen atom, an alkyl group having 1 to 8 carbon atoms, an alkoxy group having 1 to 8 carbon atoms, and an aryloxy group having 6 to 12 carbon atoms, and X1, X2 and X3 can be the same or different, and at least one is an alkyl group having 1 to 8 carbon atoms.

[0071] Examples of the alkyl group having 1 to 8 carbon atoms include methyl, ethyl, propyl, isopropyl, butyl, tert-butyl, sec-butyl, isobutyl, pentyl, 1,1-dimethylpropyl, 1,2-dimethylpropyl, neopentyl, 1-methylbutyl, 2-methylbutyl, isopentyl, hexyl, heptyl, and octyl.

[0072] Examples of the alkoxy group having 1 to 8 carbon atoms include various alkoxy groups having the above-mentioned "alkyl group having 1 to 8 carbon atoms" specifically exemplified.

[0073] Examples of the halogen atom include fluorine, chlorine, bromine and iodine, preferably fluorine, chlorine or bromine, more preferably chlorine or bromine, and particularly preferably chlorine.

[0074] In the present invention, specific examples of the organic aluminum compound include: one or more of trimethylaluminum, triethylaluminum, triisobutylaluminum, tripropylaluminum, tributylaluminum, triisopropylaluminum, tri-sec-butylaluminum, tricyclopentylaluminum, tri-n-pentylaluminum, triisopentylaluminum, trihexylaluminum, ethyldimethylaluminum, methyldiethylaluminum, tripentylaluminum, diethylaluminum chloride and dimethylaluminum chloride.

[0075] In the present invention, when the co-catalyst component is a combination of an organic boron compound and an organic aluminum compound, specific examples of the organic aluminum compound include: one or more of trimethylaluminum, triethylaluminum, triisobutylaluminum, tripropylaluminum, tributylaluminum, triisopropylaluminum, tri-sec-butylaluminum, tricyclopentylaluminum, tri-n-pentylaluminum, triisopentylaluminum, trihexylaluminum, ethyldimethylaluminum, methyldiethylaluminum and tripentylaluminum. Among them, triisobutylaluminum is preferably used.

[0076] In the present invention, when the co-catalyst component is a combination of an organoaluminum compound and an organomagnesium compound, the organoaluminum compound preferably contains at least one hydrocarbon group and at least one halogen atom, more preferably dialkylaluminum chloride, further preferably diethylaluminum chloride or dimethylaluminum chloride.

[0077] In the present invention, the organic magnesium compound is preferably an organic magnesium compound containing two alkyl groups with carbon atoms of 1 to 10, and more preferably an organic magnesium compound containing two alkyl groups with carbon atoms of 1 to 6. For example, dimethyl magnesium, diethyl magnesium, di-n-propyl magnesium, di-n-butyl magnesium, di-n-pentyl magnesium, di-n-hexyl magnesium, etc. are mentioned, among which di-n-propyl magnesium, di-n-butyl magnesium and di-n-pentyl magnesium are preferably one or more, and di-n-butyl magnesium is more preferably.

[0078] According to the present invention, when the co-catalyst component is alkylaluminoxane, the molar ratio of the transition metal compound to the alkylaluminoxane calculated as aluminum is 1:(100-20000), preferably 1:(200-10000), and more preferably 1:(500-5000).

[0079] When the co-catalyst component is a combination of an organic boron compound and an organic aluminum compound, the molar ratio of the transition metal compound to the organic boron compound is 1:(1-5), preferably 1:(1-2), and the molar ratio of the transition metal compound to the organic aluminum compound is 1:(10-5000), preferably 1:(50-1000), and more preferably 1:(100-500).

[0080] When the co-catalyst component is a combination of an organoaluminum compound and an organomagnesium compound, the molar ratio of the transition metal compound to the organoaluminum compound is 1:(30-5000), preferably 1:(100-1000), more preferably 1:(100-500), and the molar ratio of the transition metal compound to the organomagnesium compound is 1:(10-2000), preferably 1:(100-1000). In addition, the molar ratio of the organoaluminum compound to the organomagnesium compound is preferably greater than 2.5:1.

[0081] According to the present invention, preferably, the concentration of the transition metal compound in the copolymerization reaction system is 1×10 -10 mol / L~1×10 -3 mol / L, preferably 1×10 -8 mol / L~1×10 -5 mol / L.

[0082] According to the present invention, the amounts of ethylene and the allyltrimethylsilane used may be the amounts commonly used in the art for synthesizing ethylene-allyltrimethylsilane copolymers. For example, the allyltrimethylsilane concentration in the polymerization reaction system is 0.001-1 mol / L, preferably 0.005-0.5 mol / L.

[0083] In addition, the amount of olefin used may be 1,000-1,000,000 molar equivalents of the catalyst.

[0084] According to the present invention, preferably, the copolymerization reaction is carried out in an inert organic solvent. The inert organic solvent may be a mixture of one or more of a straight-chain aliphatic hydrocarbon, a branched aliphatic hydrocarbon, a substituted or unsubstituted cyclic aliphatic hydrocarbon, and a substituted or unsubstituted aromatic hydrocarbon. Specific examples of the inert organic solvent include: hexane, heptane, cyclohexane, cyclooctane, toluene, and xylene. In addition, the amount of the organic solvent may be determined according to the reaction activity to ensure that the produced polymer is well dissolved in the system, at least without affecting the dispersion.

[0085] According to the method of the present invention, the copolymerization reaction conditions can be the common conditions used in the art for synthesizing ethylene-allyltrimethylsilane copolymers. Preferably, the copolymerization reaction temperature is -50 to 200°C, and the copolymerization reaction time is 1 to 300 minutes; more preferably, the copolymerization reaction temperature is -20 to 150°C, and the copolymerization reaction time is 5 to 60 minutes.

[0086] According to the method of the present invention, preferably, the partial pressure of ethylene is 0.1-10 MPa, preferably 0.1-4.0 MPa.

[0087] In the present invention, the transition metal compound can be synthesized according to conventional methods in the art. In a preferred embodiment of the present invention, when X and Y in formula (1) are each independently a hydrocarbon oxy group having 1 to 10 carbon atoms, the preparation method of the transition metal compound comprises: in an inert atmosphere and in the presence of a first organic solvent, a first contact reaction is carried out between 10-hydroxybenzo[H]quinoline and a compound represented by the general formula MA4 (hereinafter referred to as method 1).

[0088] In method 1, in the compound represented by the general formula MA4, M is a tetravalent transition metal atom; and A is independently a hydrocarbonoxy group having 1 to 10 carbon atoms.

[0089] Preferably, M is a titanium atom, a zirconium atom or a hafnium atom, more preferably a titanium atom or a zirconium atom.

[0090] Preferably, each A is independently a hydrocarbyloxy group having 1 to 6 carbon atoms; more preferably, each A is independently a hydrocarbyloxy group having 1 to 3 carbon atoms.

[0091] Examples of the hydrocarbonoxy group having 1 to 10 carbon atoms include methoxy, ethoxy, propoxy, isopropoxy, butoxy, tert-butoxy, sec-butoxy, isobutoxy, pentyloxy, and hexyloxy. Among them, methoxy, ethoxy, propoxy, and isopropoxy are preferred, ethoxy, propoxy, and isopropoxy are more preferred, and ethoxy and isopropoxy are still more preferred.

[0092] In method 1, the molar ratio of 10-hydroxybenzo[H]quinoline to the compound represented by the general formula MA4 can be 1.8-2.2:1, preferably 1.9-2.1:1, and more preferably 1.95-2.05:1.

[0093] In method 1, the first organic solvent may be an organic solvent that is inert to the reaction raw materials and can dissolve the reaction raw materials, for example, toluene may be used. The amount of the organic solvent may be selected according to the amount of 10-hydroxybenzo[H]quinoline, for example, the amount of the first organic solvent relative to 1 mol of 10-hydroxybenzo[H]quinoline is 5-30 L, preferably 6-20 L, more preferably 7-15 L, and particularly preferably 8-10 L.

[0094] In method 1, the inert atmosphere may be implemented by using nitrogen gas and / or argon gas.

[0095] In method 1, the conditions of the first contact reaction can be selected according to the boiling point of the first organic solution used, for example, the reaction can be carried out under reflux conditions for 5-20 hours, preferably 5-10 hours.

[0096] In method 1, after the first contact reaction is completed, the product may be purified by a conventional purification method in the art. For example, after the first contact reaction is completed, the solvent may be removed and washing may be performed to obtain the target product.

[0097] In a preferred embodiment of the present invention, after the first contact reaction is completed, the solvent is removed, and then centrifugal washing is performed 2-3 times using ice-cold hexane to obtain the target product.

[0098] In addition, when X and Y in formula (1) are each independently a halogen, the preparation method of the transition metal compound comprises: in an inert atmosphere and in the presence of a second organic solvent, subjecting 10-hydroxybenzo[H]quinoline to a second contact reaction with an n-butyllithium solution, and then subjecting it to a third contact reaction with a compound represented by MX4 (hereinafter referred to as method 2).

[0099] In method 2, in the compound represented by the general formula MX4, M is a tetravalent transition metal atom; and X is independently a halogen.

[0100] Preferably, M is a titanium atom, a zirconium atom or a hafnium atom, more preferably a titanium atom or a zirconium atom.

[0101] Examples of the halogen atom include fluorine, chlorine, bromine and iodine, preferably fluorine, chlorine or bromine, more preferably chlorine or bromine, and particularly preferably chlorine.

[0102] In method 2, the molar ratio of 10-hydroxybenzo[H]quinoline to n-butyllithium can be 1:0.95-1.5, preferably 1:1-1.2, and more preferably 1:1-1.1.

[0103] As the above-mentioned n-butyl lithium solution, for example, n-butyl lithium hexane solution can be used. When used in the form of a solution, the content of n-butyl lithium in the solution can be, for example, 1-3 mol / L, preferably 2-3 mol / L, and more preferably 2-2.5 mol / L.

[0104] In method 2, the second organic solvent may be an organic solvent that is inert to the reaction raw materials and can dissolve the reaction raw materials, for example, toluene may be used. The amount of the organic solvent may be selected according to the amount of 10-hydroxybenzo[H]quinoline, for example, relative to 1 mol of 10-hydroxybenzo[H]quinoline, the amount of the first organic solvent is 5-30 L, preferably 6-20 L, more preferably 7-15 L, and particularly preferably 7-9 L.

[0105] In method 2, the inert atmosphere may be implemented by using nitrogen and / or argon.

[0106] In method 2, the second contact reaction is preferably carried out by dropwise adding an n-butyl lithium solution into a mixed solution of 10-hydroxybenzo[H]quinoline and the second organic solvent.

[0107] The temperature of the second contact reaction during the dropwise addition may be -30 to 0° C., preferably -20 to -10° C. After the dropwise addition is completed, the reaction may be carried out at room temperature (eg, 10 to 40° C.) for 5 to 36 hours, preferably 12 to 24 hours.

[0108] In method 2, the molar ratio of 10-hydroxybenzo[H]quinoline to the compound represented by the general formula MX4 can be 1.8-2.2:1, preferably 1.9-2.1:1, and more preferably 1.95-2.05:1.

[0109] In method 2, the third contact reaction is preferably carried out by dropwise adding the n-butyllithium solution into the product of the first contact reaction to carry out the third contact reaction.

[0110] The temperature of the third contact reaction during the dropwise addition may be -30 to 0° C., preferably -20 to -10° C. After the dropwise addition is completed, the reaction may be carried out at room temperature (eg, 10 to 40° C.) for 5 to 36 hours, preferably 12 to 24 hours.

[0111] In method 2, after the third contact reaction is completed, the product may be purified by a conventional purification method in the art. For example, after the third contact reaction is completed, the solvent may be removed and washing may be performed to obtain the target product.

[0112] In a preferred embodiment of the present invention, after the third contact reaction is completed, a solid phase is obtained by solid-liquid separation, and centrifugation washing is performed 2-3 times using ice-cold hexane to obtain the target product.

[0113] In addition, in the present invention, the target product in method 2 can be prepared by replacing the hydrocarbon group with 1-10 carbon atoms in the target product obtained by method 1 with a halogen group; similarly, the target product in method 2 can be prepared by replacing the halogen group with a hydrocarbon group with 1-10 carbon atoms. The specific method can be implemented by conventional synthesis methods in the art.

[0114] According to a second aspect of the present invention, there is provided an ethylene-allyltrimethylsilane copolymer prepared by the method for preparing the ethylene-allyltrimethylsilane copolymer according to the first aspect of the present invention.

[0115] The present invention will be described in detail below by way of examples, but the present invention is not limited to the following examples.

[0116] The raw materials used in the following examples and comparative examples, unless otherwise specified, are all disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation method disclosed in the prior art.

[0117] In the following examples and comparative examples, the comonomer content was tested using the following method.

[0118] The comonomer content of the sample was tested using an AVANCE III 400MHz nuclear magnetic resonance spectrometer produced by Bruker. The solvent was deuterated o-dichlorobenzene, and a 10 mm PASEX 13C-1H / D Z-GRD probe was used to dissolve a sample with a mass concentration of 10% at 130°C. The test temperature was 125°C, the rotation speed was 20 Hz, the pulse was 90°, the spectrum width was 120 ppm, the sampling time was 5 seconds, the delay time was 10 seconds, and the scan was 6000 times. 13 The comonomer content was calculated from the C-NMR spectrum using the method described in the literature (e.g. Macromolecules 2008, 41(4), 1070-1072).

[0119] Preparation Example 1

[0120] Synthesis of compound (1):

[0121]

[0122] Place the magnet in a dry 250 ml three-necked flask, and place the reaction flask on a device with magnetic stirring and oil bath heating. After evacuating the three-necked flask, rinse it repeatedly with nitrogen three times, add 470 mg of 10-hydroxybenzo[H]quinoline under nitrogen atmosphere, add 20 ml of toluene and stir at room temperature to dissolve; add 10 ml of toluene solution of tetra(isopropoxy)titanium (containing 342 mg of tetra(isopropoxy)titanium) and stir evenly. Then, under nitrogen protection, add a condenser with room temperature water as the cooling medium. Control the oil bath temperature at 115-130°C and allow the reaction to proceed for 8 hours under toluene reflux. Then remove the reflux condenser, install a distillation device, maintain the temperature, and evaporate the liquid of the reaction mixture until a yellow solid or viscous substance is obtained, and then cool it to room temperature. Under nitrogen protection, add 10 ml of cold hexane, mix thoroughly, and centrifuge the resulting slurry. Pour out the supernatant. Add 10 ml of cold hexane again, mix thoroughly, and centrifuge the resulting slurry. The supernatant was poured off, and the solvent of the obtained solid was removed under vacuum to obtain 641 mg of bright yellow solid with a molar yield of 96%.

[0123] 1 H-NMR(in CDCl3,d=):9.09-9.11(2H),7.71-7.73(2H),7.52-7.56(2H),7.46-7.49 (2H),7.14-7.19(6H),6.89-6.92(2H),4.84-4.91(2H),1.07-1.19(12H).

[0124] 13 C-NMR (in CDCl3, d=): 161.3, 148.9, 143.7, 135.9, 134.5, 128.8, 127.9, 125.3, 123.3, 118.8, 118.5, 116.5, 115.4, 77.0, 24.3.

[0125] Preparation Example 2

[0126] Synthesis of compound (2):

[0127]

[0128] Place the magnet in a dry 250 ml three-necked flask, evacuate the flask and rinse it with nitrogen three times, add 500 mg of 10-hydroxybenzo[H]quinoline under nitrogen atmosphere, add 20 ml of toluene and stir at room temperature to dissolve, place the three-necked flask in a low-temperature magnetic stirring device, and stir at -20°C for 20 minutes. Take 1.1 ml of n-butyl lithium solution (2.5 mol / L hexane solution) and slowly add it dropwise. After the addition is complete, naturally warm to room temperature and stir to react overnight. Place the three-necked flask in a low-temperature magnetic stirring device and stir at -20°C for 20 minutes. Dissolve 243 mg of titanium tetrachloride in 10 ml of toluene at -20°C and slowly add it dropwise to the three-necked flask. After the addition is complete, naturally warm to room temperature and stir to react overnight. The obtained reaction slurry was filtered through diatomaceous earth, and the filter cake was washed with toluene. The obtained dark red solution was desolventized under vacuum to obtain a dark red solid. 10 ml of cold hexane was added, and after thorough mixing, the obtained slurry was centrifuged and the supernatant was poured out. 10 ml of cold hexane was added again, and after thorough mixing, the obtained slurry was centrifuged and the supernatant was poured out. The obtained solid was desolventized under vacuum to obtain 590 mg of a dark red solid with a molar yield of 91%.

[0129] The structure of the dark red solid was confirmed to be compound (2) by H-NMR and C-NMR.

[0130] Preparation Example 3

[0131] Synthesis of compound (3):

[0132]

[0133] Place the magnet in a dry 250 ml three-necked flask, evacuate the flask and rinse it with nitrogen three times, add 586 mg of 10-hydroxybenzo[H]quinoline under nitrogen atmosphere, add 20 ml of toluene and stir at room temperature to dissolve, place the three-necked flask in a low-temperature magnetic stirring device, and stir at -20°C for 20 minutes. Take 1.3 ml of n-butyl lithium solution (2.5 mol / L hexane solution) and slowly add it dropwise. After the addition is complete, warm to room temperature naturally and stir to react overnight. Place the three-necked flask in a low-temperature magnetic stirring device and stir at -20°C for 20 minutes. Under nitrogen protection, add 350 mg of zirconium tetrachloride solid to the three-necked flask three times, with an interval of 2 minutes each time. After completion, warm to room temperature naturally and stir to react overnight. The obtained reaction slurry was filtered through diatomaceous earth, and the filter cake was washed with toluene. The obtained red solution was freed of solvent under vacuum to obtain a red solid. 10 ml of cold hexane was added and mixed thoroughly. The obtained slurry was centrifuged and the supernatant was poured out. 10 ml of cold hexane was added again and mixed thoroughly. The obtained slurry was centrifuged and the supernatant was poured out. The obtained solid was freed of solvent under vacuum to obtain 675 mg of dark red solid with a molar yield of 82%.

[0134] The structure of the dark red solid was confirmed to be compound (3) by H-NMR and C-NMR.

[0135] Preparation Example 4

[0136] Synthesis of compound (4):

[0137]

[0138] Place the magnet in a dry 250 ml three-necked flask, and place the reaction flask on a device for magnetic stirring and oil bath heating. After evacuating the three-necked flask, rinse it repeatedly with nitrogen three times. Add 426 mg of 10-hydroxybenzo[H]quinoline, 296 mg of tetra(ethoxy)zirconium, and 20 ml of toluene under a nitrogen atmosphere, and stir evenly at room temperature. Then, under nitrogen protection, add a condenser with room temperature water as the cooling medium. Control the oil bath temperature at 115-130°C and allow the reaction to proceed under toluene reflux for 18 hours. Cool to room temperature, filter the solution, and remove the solvent in vacuum to obtain a light yellow solid or viscous material. Under nitrogen protection, add 10 ml of cold hexane, mix thoroughly, centrifuge the resulting slurry, pour out the supernatant, and remove the solvent from the resulting solid under vacuum to obtain 482 mg of a light yellow solid with a molar yield of 78%.

[0139] The structure of the light yellow solid was confirmed to be compound (4) by hydrogen and carbon nuclear magnetic spectra.

[0140] Preparation Example 5

[0141] Synthesis of compound (5):

[0142]

[0143] Place the magnet in a dry 250 ml three-necked flask, evacuate the flask and rinse it with nitrogen three times, add 575 mg of 10-hydroxybenzo[H]quinoline under nitrogen atmosphere, add 20 ml of toluene and stir at room temperature to dissolve, place the three-necked flask in a low-temperature magnetic stirring device, and stir at -20°C for 20 minutes. Take 1.3 ml of n-butyl lithium solution (2.5 mol / L hexane solution) and slowly add it dropwise. After the addition is complete, naturally warm to room temperature and stir to react overnight. Place the three-necked flask in a low-temperature magnetic stirring device and stir at -20°C for 20 minutes. Under nitrogen protection, add 470 mg of zirconium tetrachloride solid to the three-necked flask three times, with an interval of 2 minutes each time. After completion, naturally warm to room temperature and stir to react overnight. The obtained reaction slurry was filtered through diatomaceous earth, and the filter cake was washed with toluene. The obtained red solution was desolventized under vacuum to obtain a red solid. 10 ml of cold hexane was added and mixed thoroughly. The obtained slurry was centrifuged and the supernatant was poured out. 10 ml of cold hexane was added again and mixed thoroughly. The obtained slurry was centrifuged and the supernatant was poured out. The obtained solid was desolventized under vacuum to obtain 712 mg of dark red solid with a molar yield of 76%.

[0144] The structure of the dark red solid was confirmed to be compound (5) by H-NMR and C-NMR.

[0145] Example 1

[0146] Copolymerization of ethylene and allyltrimethylsilane using compound (1) as catalyst

[0147] A 250 ml glass polymerization bottle that has been thoroughly dried was evacuated and flushed with nitrogen, and this process was repeated three times. Evacuate the bottle and fill it with ethylene, the ethylene pressure being 1.05 standard atmospheres. 25 ml of toluene, 1 ml of allyltrimethylsilane, and 3 ml of methylaluminoxane toluene solution (containing 5.0 mmol of methylaluminoxane) were added in sequence. Stirring and heating were started, and the temperature was set to 70°C. When the temperature reached 70°C, 1 ml of catalyst toluene solution (containing 5 micromoles of compound (1)) was added, and the timing was started. When ethylene was consumed, ethylene was replenished to keep the ethylene pressure at a constant 1.05 standard atmospheres. After 20 minutes, the ethylene was turned off, and the reaction solution was poured into a beaker. 300 ml of anhydrous ethanol and 5 ml of concentrated hydrochloric acid were added, and the mixture was stirred for 6 hours. The polymer was filtered and dried under vacuum at 60°C for 24 hours to obtain 0.89 g of polymer. The polymerization activity was 534 kg polymer / mol catalyst / hour, and the results were confirmed by nuclear magnetic resonance. 13 The allyltrimethylsilane content was determined by C-NMR and was 5.4 mol%.

[0148] Example 2

[0149] Copolymerization of ethylene and allyltrimethylsilane using compound (1) as catalyst

[0150] A 250 ml glass polymerization bottle was fully dried, evacuated, and flushed with nitrogen, and repeated three times. Evacuated, filled with ethylene, the ethylene pressure was 1.05 standard atmospheric pressure, 26 ml toluene, 1 ml allyl trimethylsilane, 1 ml triisobutylaluminum toluene solution (containing 1.0 mmol triisobutylaluminum) were added in sequence, stirring and heating were started, and the temperature was set to 70°C. When the temperature rose to 70°C, 1 ml catalyst toluene solution (containing 5 micromoles of compound (1)) was added. After 3 minutes, 1 ml triphenylmethyl tetrakis (pentafluorophenyl) borate toluene solution (containing 7.5 micromoles of triphenylmethyl tetrakis (pentafluorophenyl) borate) was added, and timing was started. When ethylene was consumed, ethylene was replenished to keep ethylene at a constant standard atmospheric pressure of 1.05. After 20 minutes, ethylene was turned off, the reaction solution was poured into a beaker, 300 ml anhydrous ethanol and 5 ml concentrated hydrochloric acid were added, stirred for 6 hours, filtered to obtain a polymer, and vacuum dried at 60°C for 24 hours to obtain 0.82 g of a polymer. Polymerization activity 492 kg polymer / mol catalyst / hour, by NMR 13 The allyltrimethylsilane content was determined by C-NMR and was 5.9 mol%.

[0151] Example 3

[0152] Copolymerization of ethylene and allyltrimethylsilane using compound (1) as catalyst

[0153] A 250 ml glass polymerizer bottle was dried thoroughly, evacuated, and flushed with nitrogen, and repeated three times. Evacuated, filled with ethylene, the ethylene pressure was 1.05 standard atmospheric pressure, 25 ml of toluene, 1 ml of allyltrimethylsilane, 2.5 ml of diethylaluminum chloride toluene solution (containing 2.5 mmol of diethylaluminum chloride) were added in sequence, stirring and heating were started, and the temperature was set to 70°C. When the temperature rose to 70°C, 1 ml of catalyst toluene solution (containing 5 micromoles of compound (1)) was added. After 3 minutes, 0.5 ml of di-n-butylmagnesium toluene solution (containing 0.5 mmol of di-n-butylmagnesium) was added, and timing was started. When ethylene was consumed, ethylene was replenished to keep the ethylene pressure constant at 1.05 standard atmospheric pressure. After 20 minutes, ethylene was turned off, the reaction solution was poured into a beaker, 300 ml of anhydrous ethanol and 5 ml of concentrated hydrochloric acid were added, and the mixture was stirred for 6 hours. The polymer was filtered and dried under vacuum at 60°C for 24 hours to obtain 0.94 g of polymer. Polymerization activity 564 kg polymer / mol catalyst / hour, by NMR 13 The allyltrimethylsilane content was determined by C-NMR and was 3.2 mol%.

[0154] Example 4

[0155] Copolymerization of ethylene and allyltrimethylsilane using compound (1) as catalyst

[0156] A 100 ml stainless steel polymerization kettle that has been fully dried is heated to 55°C in an empty state and evacuated for 30 minutes. Ethylene is introduced to maintain a weak ethylene flow. 30 ml of n-hexane, 5 ml of allyltrimethylsilane, 2.5 ml of diethylaluminum chloride hexane solution (containing 2.5 mmol of diethylaluminum chloride) are added, stirring is started, the temperature is adjusted to 60°C, 1 ml of catalyst toluene solution (containing 2 micromoles of compound (1)) is added, and after 3 minutes, after stabilization at 60°C, 0.5 ml of di-n-butylmagnesium toluene solution (containing 0.5 mmol of di-n-butylmagnesium) is added, and the feed port is closed. The ethylene pressure is adjusted to 6 standard atmospheres. After 30 minutes, the ethylene is turned off, the temperature is lowered, the pressure is slowly released, and the polymer is taken out. The polymer is soaked in 300 mL of anhydrous ethanol, filtered to obtain the polymer, and vacuum dried at 60°C for 24 hours to obtain 9.52 g of polymer. The polymerization activity is 9520 kg polymer / mol catalyst / hour, and the results are shown by nuclear magnetic resonance. 13 The allyltrimethylsilane content was determined by C-NMR and was 6.2 mol%.

[0157] Example 5

[0158] Copolymerization of ethylene and allyltrimethylsilane using compound (2) as catalyst

[0159] The method of Example 1 was followed, except that compound (1) was replaced by the same molar amount of compound (2), and 0.91 g of polymer was obtained in the same manner. The polymerization activity was 546 kg polymer / mol catalyst / hour, and the results of nuclear magnetic resonance spectroscopy showed that the polymerization activity was 546 kg polymer / mol catalyst / hour, and ... 13 The allyltrimethylsilane content was determined by C-NMR and was 5.1 mol%.

[0160] Example 6

[0161] Copolymerization of ethylene and allyltrimethylsilane using compound (3) as catalyst

[0162] The method of Example 1 was followed, except that compound (1) was replaced by the same molar amount of compound (3), and 1.01 g of polymer was obtained in the same manner. The polymerization activity was 606 kg polymer / mol catalyst / hour, and the results of nuclear magnetic resonance spectroscopy showed that the polymerization activity was 606 kg polymer / mol catalyst / hour, and ... 13 The allyltrimethylsilane content was determined by C-NMR and was 4.9 mol%.

[0163] Example 8

[0164] Copolymerization of ethylene and allyltrimethylsilane using compound (4) as catalyst

[0165] The method of Example 1 was followed, except that the compound (1) was replaced by the same molar amount of the compound (4), and 1.00 g of polymer was obtained in the same manner. The polymerization activity was 600 kg polymer / mol catalyst / hour, and the results were confirmed by nuclear magnetic resonance.13 The allyltrimethylsilane content was determined by C-NMR and was 5.5 mol%.

[0166] Example 9

[0167] Copolymerization of ethylene and allyltrimethylsilane using compound (5) as catalyst

[0168] The method of Example 1 was followed, except that compound (1) was replaced by the same molar amount of compound (5), and 0.94 g of polymer was obtained in the same manner. The polymerization activity was 564 kg polymer / mol catalyst / hour, and the results of nuclear magnetic resonance spectroscopy showed that the polymerization activity was 564 kg polymer / mol catalyst / hour, and ... 13 The allyltrimethylsilane content was determined by C-NMR and was 6.1 mol%.

[0169] Comparative Example 1

[0170] Copolymerization of Ethylene and Allyltrimethylsilane Catalyzed by Zirconocene Dichloride

[0171] The method of Example 7 was followed, except that compound (1) was replaced by the same molar amount of zirconocene dichloride, and 0.40 g of polymer was obtained. The polymerization activity was 240 kg polymer / mol catalyst / hour, and the results were analyzed by nuclear magnetic resonance. 13 The allyltrimethylsilane content was determined by C-NMR and was 2.7 mol%.

[0172] Comparative Example 2

[0173] Copolymerization of Ethylene and Allyltrimethylsilane Catalyzed by Zirconocene Dichloride

[0174] The method of Example 8 was followed, except that compound (1) was replaced by the same molar amount of zirconocene dichloride, and 0.42 g of polymer was obtained. The polymerization activity was 252 kg polymer / mol catalyst / hour, and the results were analyzed by nuclear magnetic resonance. 13 The allyltrimethylsilane content was determined by C-NMR and was 2.9 mol%.

[0175] Comparative Example 3

[0176] Copolymerization of Ethylene and Allyltrimethylsilane Catalyzed by Zirconocene Dichloride

[0177] The method of Example 9 was followed, except that the compound (1) was replaced by the same molar amount of zirconocene dichloride, and 0.03 g of polymer was obtained in the same manner. The polymerization activity was 18 kg polymer / mol catalyst / hour.

[0178] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing an ethylene-allyltrimethylsilane copolymer, characterized in that: The method comprises: using a catalyst composition to copolymerize ethylene and allyltrimethylsilane, Wherein, the catalyst composition comprises the following components: a) a transition metal compound having a structure represented by formula (1); b) a co-catalyst component, In formula (1), M is a tetravalent transition metal atom; X and Y are each independently a hydrocarbonoxy group having 1 to 10 carbon atoms or a halogen.

2. The method according to claim 1, wherein: X and Y are each independently a hydrocarbonoxy group having 1 to 6 carbon atoms, a fluorine atom, a chlorine atom, a bromine atom or an iodine atom, preferably a hydrocarbonoxy group having 1 to 3 carbon atoms or a chlorine atom; Preferably, the alkoxy group having 1 to 10 carbon atoms is methoxy, ethoxy, propoxy or isopropoxy.

3. The method according to claim 1, wherein: M is a titanium atom, a zirconium atom or a hafnium atom, and is preferably a titanium atom or a zirconium atom.

4. The method according to any one of claims 1 to 3, wherein: X and Y are both isopropoxy or ethoxy; or, X and Y are both chlorine atoms.

5. The method according to any one of claims 1 to 3, wherein: The co-catalyst component includes an alkylaluminoxane, a combination of an organic boron compound and an organic aluminum compound, or a combination of an organic aluminum compound and an organic magnesium compound; Preferably, the co-catalyst component is an alkylaluminoxane, a combination of an organic boron compound and an organic aluminum compound, or a combination of an organic aluminum compound and an organic magnesium compound.

6. The method according to claim 5, wherein: The organoaluminum compound is a compound having a structure represented by the general formula AlX1X2X3, wherein X1, X2 and X3 are respectively a halogen atom, an alkyl group having 1 to 8 carbon atoms, an alkoxy group having 1 to 8 carbon atoms, and an aryloxy group having 6 to 12 carbon atoms, and X1, X2 and X3 may be the same or different, and at least one of them is an alkyl group having 1 to 8 carbon atoms; Preferably, the organoaluminum compound is triisobutylaluminum.

7. The method according to claim 5, wherein: The organic boron compound is one or more of triphenylmethyl tetrakis(pentafluorophenyl)borate, N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate and tris(pentafluorophenyl)boron.

8. The method according to claim 5, wherein: The alkylaluminoxane is a compound selected from the group consisting of compounds represented by formula (2) and / or formula (3), In formula (2) and formula (3), R is selected from an alkyl group having 1 to 15 carbon atoms, and n represents an integer of 4 to 30; Preferably, R is selected from an alkyl group having 1 to 5 carbon atoms, and n represents an integer of 10 to 30; Preferably, the alkylaluminoxane is methylaluminoxane.

9. The method according to claim 5, wherein: The organomagnesium compound is an organomagnesium compound containing two alkyl groups with carbon atoms of 1 to 10, preferably an organomagnesium compound containing two alkyl groups with carbon atoms of 1 to 6, and more preferably di-n-butylmagnesium.

10. The method according to claim 5, wherein: The co-catalyst component is alkylaluminoxane, and the molar ratio of the transition metal compound to the alkylaluminoxane calculated on the basis of aluminum is 1:(100-20000), preferably 1:(200-10000), and more preferably 1:(500-5000).

11. The method according to claim 5, wherein: The co-catalyst component is a combination of an organic boron compound and an organic aluminum compound, the molar ratio of the transition metal compound to the organic boron compound is 1:(1-5), preferably 1:(1-2), the molar ratio of the transition metal compound to the organic aluminum compound is 1:(10-5000), preferably 1:(50-1000), more preferably 1:(100-500).

12. The method according to claim 5, wherein: The co-catalyst component is a combination of an organoaluminum compound and an organomagnesium compound, the molar ratio of the transition metal compound to the organoaluminum compound is 1:(30-5000), preferably 1:(100-1000), more preferably 1:(100-500), and the molar ratio of the transition metal compound to the organomagnesium compound is 1:(10-2000), preferably 1:(100-1000); Preferably, the molar ratio of the organoaluminum compound to the organomagnesium compound is greater than 2.5:

1.

13. The method according to any one of claims 1 to 3, wherein: The copolymerization reaction temperature is -50 to 200°C, and the copolymerization reaction time is 1 to 300 minutes; Preferably, the copolymerization reaction temperature is -20 to 150° C., and the copolymerization reaction time is 5 to 60 minutes.

14. The method according to any one of claims 1 to 3, wherein:The concentration of the transition metal compound in the copolymerization reaction system is 1×10 -10 mol / L~1×10 -3 mol / L, preferably 1×10 -8 mol / L~1×10 -5 mol / L.

15. Ethylene-allyltrimethylsilane copolymer prepared by the method for preparing the ethylene-allyltrimethylsilane copolymer according to any one of claims 1 to 14.

Citation Information

Patent Citations

  • Olefin copolymer and preparation method thereof

    CN107973870A

  • Copolymerization method of ethylene and alkenyl-terminated silane / siloxane as well as copolymer and application thereof

    CN115260360A

  • Olefin polymerization catalysts, transition metal compounds, processes for olefin polymerization, and alpha-olefin / conjugated diene copolymers

    CN1199052A

  • Process for copolymerizing ethylene with vinylsilanes

    CN1863831A

  • New Transition metal complexes, catalysts composition containing the same, and methods for preparing ethylene homopolymers or copolymers of ethylene and α-olefins using the same

    KR1020120097030A